HOW TO DEVELOP THE STANDARDIZED INSTRUMENTS OF MULTIPLE INTELLIGENCES IN ELEMENTARY SCHOOL: A QUALITATIVE-DESCRIPTIVE APPROACH - Tria Mardiana; Indiati Indiati (The University of Kuningan, 2020)
It was rarely the academicians, and practitioners knew how to make the standardized instruments to analyze the student's multiple intelligences. The purpose of this study was to describe the development of a standardized instrument of multiple intelligences for children in elementary school. The research method used was descriptive qualitative. In qualitative research, the research instrument was the researcher himself. The research instrument was not external or objective, but internal or subjective, namely the researcher himself without using tests, questionnaires, or experiments. Therefore the direct presence of researchers was a necessity in qualitative research. The data collection techniques used were observation and documentation. The results obtained in this study were to identify multiple intelligences in 7-12 years old children, we could use standardized instruments based on the classification of children's multiple intelligences. To analyze the development of multiple intelligences of 7-12 years old children, we could use the major theory of Gardner and Armstrong. The development of standard instruments used to measure multiple intelligences of 7-12 years old children, we could use 13 steps of Jamaris theory. This development step unravels the theory, determines the basis, then turns it into a standardized instrument that can be used to measure the type of multiple intelligences in 7-12 years old children. How to use the standardized instruments and its recommendations for teachers are discussed.Keywords:multiple intelligences; standardized instrument; development